Double‐Network Confined Supramolecular Phosphorescence Light‐Harvesting Boosting Photocatalysis. Issue 23 (18th September 2022) - Yu, Jie; Wang, Hui; Liu, Yu
Abstract: A double‐network phosphorescence light‐harvesting (PLH) supramolecular system is successfully fabricated based on synergistic confinement strategy. First, the bicationic vinyl bromophenyl pyridine derivative (G) is encapsulated by cucurbit[8]uril (CB[8]), inducing weak phosphorescence emission at 510 nm. Subsequently, the G/CB[8] is confined by in situ copolymerization with acrylamide, displaying enhanced phosphorescence emission, then coassembled with hyaluronic acid modified hydroxypropyl‐β‐cyclodextrin (HA‐HP‐β‐CD) to form double‐network hydrogel, further improving phosphorescence lifetime from 442 µs upto 5.17 ms. Benefitting from the confinement of double‐network of supramolecular system, the doped Eosin Y (EY) as acceptor can be photosensitized by the phosphorescence of G/CB[8] leading to delayed fluorescence emission of EY with long lifetime as 36.4 µs. As compared with EY alone, by the synergistic effect of the confined microenvironment and long lifetime photosensitizer, the PLH system is successfully applied in cross‐coupling reaction and exhibits enhanced activity, providing a new strategy for the application of phosphorescence energy transfer boosting photocatalysis. Abstract : A confined phosphorescence light‐harvesting (PLH) system is successfully fabricated by in situ copolymerization of CB[8]/vinyl bromophenyl pyridine derivative, acrylamide, and HA‐HP‐β‐CD. Based on the triple confinement of CB[8], polymerization and assembly, the double‐network hydrogel not only shows efficient phosphorescence emission, but also can bind with Eosin Y (EY) as acceptor to form PLH system with delayed fluorescence emission and photocatalysis performance.